Arousing Motives or Eliciting Stories? On the Role of Pictures in a Picture–Story Exercise. (April 2023) - Schäpers, Philipp; Krumm, Stefan; Lievens, Filip; Stenzel, Nikola
Picture–story exercises (PSE) form a popular measurement approach that has been widely used for the assessment of implicit motives. However, current theorizing offers two diverging perspectives on the role of pictures in PSEs: either to elicit stories or to arouse motives. In the current study, we tested these perspectives in an experimental design. We administered a PSE either with or without pictures. Results from N = 281 participants revealed that the experimental manipulation had a medium to large effect for the affiliation and power motive domains, but no effect for the achievement motive domain. We conclude that the herein chosen pictures cues function differentially across motives, as they aroused the affiliation and power motives, but not the achievement motive.